Campaña de comunicación integral para la Asociación Peruana de Agencias de Viajes y Turismo - APAVIT Perú - Enriquez Vivanco, Almendra Jasmine (2020)
The following project proposes an integrated communications campaign for the Peruvian Travel and Tourism Agencies Association - APAVIT. The campaign objectives are the following: to make the association known, to strengthen its image within the sector, to communicate the benefits of traveling through travel agencies and to motivate the target audience to continue traveling while hiring the services of a travel and tourism agency. To achieve this, an analysis of the current global context was made in the context of the pandemic caused by the COVID-19 virus along with a survey and in-depth interviews to a sample of the target audience. Subsequently, the campaign strategy and creative pieces are presented to achieve the objectives in the most effective way possible, highlighting the value of reliability, security and responsibility.